PNEUMONECTOMY IN THE PATIENTS WITH THE COMPLICATED COURSE OF WEGENER'S GRANULOMATOSIS - M. A. Bagirov; T. K. Tokaev; A. S. Zaytseva; K. V. Tokaev; Yu. A. Evdokimov; V. A. Khomenko (Туберкулез и болезни лёгких)
The article describes a clinical case of 42-year old male patient with necrotising granulomatosis with polyangitis (Wegener's granulomatosis) complicated by pulmonary aspergillosis, and due to the latter a life-saving pneumonectomy had to be done  Microbiological tests of surgery specimens detected the cell crowding of mold fungi of Aspergillus fumigatus The histological tests showed necrotising granulomatosis with polyangitis, formation of cavities with fibrotic walls and fungal population; fibrinous-hemorrhagic pleurisy. In one month after surgery the patient was transferred to the rheumatological ward, where biological anti-B-cellular therapy with rituximab was started with a consequent positive outcome.